Assessing spatial and temporal variability for some edaphic characteristics of Mediterranean rainfed and irrigated soils - Telo da Gama, José (2019)
Mediterranean soils are particularly threatened by salinization and low levels of organic matter content. In order to assess an edaphic sustainable use, we need to study its characteristics and better understand the temporal and spatial evolution. In this study, a total of 14,852 ha located in a western Mediterranean basin were selected as the study site where 1417 and 1451 topsoil samples were analyzed in 2001/2002 and 2011/2012, respectively, for Soil Organic Matter (SOM) content, pH water (pH(w)) and electrical conductivity (EC). Classical statistics and geostatistics techniques were used and the individual soil samples were related with the cultural system (CS) practiced-rainfed/irrigation-and the Reference Soil Group (RSG)-Cambisols, Calcisols, Luvisols, and Fluvisols. Predictive maps were created by interpolation using the Ordinary Kriging algorithm. The main results of this study were that, when transitioning from a rainfed to irrigation CS, SOM content is maintained in Cambisols but decreases in the other RSGs, pH(w) is maintained and EC increases in Fluvisols, Luvisols, and Cambisols. Over time in the rainfed CS all RSGs maintained SOM and pH(w) but EC increased in Fluvisols, Luvisols, and Calcisols and in the irrigation CS SOM decreased in Luvisols, pH(w) increased in Fluvisols and Calcisols and EC increased in all RSGs.